Case Report: Concurrent transcatheter aortic and mitral valve replacement for symptomatic concomitant aortic and mitral valve stenoses - Bussmann, Benjamin Mothibe; Dawkins, Sam; Newton, James; Cahill, Thomas (Frontiers in Cardiovascular Medicine, 2024)
In patients undergoing transcatheter aortic valve implantation (TAVI), multi-valve disease is common and associated with worse outcomes. Despite multiple emerging transcatheter valve treatment options, no guidelines exist for the transcatheter treatment of multi-valve disease. We present a case of a 76-year-old patient with concomitant severe aortic valve stenosis and severe mitral valve stenosis who underwent concurrent TAVI and transcatheter mitral valve replacement. In this case report, we demonstrate the feasibility of concurrent double-valve transcatheter intervention to treat patients with multi-valve disease. We also highlight the role of the heart valve team to guide individual patient treatment strategies in the absence of clinical guidelines and the importance of multi-modality imaging to plan and execute the procedure.